Kajian dampak pengadaan layanan bimbingan dan konseling terhadap sikap dan perilaku positif siswa di MTs Al-Maarif 02 Singosari - Wakindiyah, Nimas Yuhyih (Maliki Interdisciplinary Journal, 2024)
Guidance and counseling services have an important role in shaping students’ attitudes and behavior, which in the end can influence their academic achievement and overall well-being. This research explores the impact of providing guidance and counseling services at MTs Almaarif O2 Singosari. With the aim of understanding the basic mechanisms that drive positive change in students. This research seeks to examine how guidance and counseling services at MTs Almaarif 02 Singosari contribute to fostering a supportive environment for students. The results of this research show that there are significant changes in students’ attitudes and behavior after participating in guidance and counseling services. This finding shows that guidance and counseling services have a positive impact in improving student attitudes and behavior at MTs Almaarif 02 Singosari.